2013
DOI: 10.3897/jhr.32.4646
|View full text |Cite
|
Sign up to set email alerts
|

Nesting biology and phenology of a population of Halictus farinosus Smith (Hymenoptera, Halictidae) in northern Utah

Abstract: Nesting biology and phenology in an aggregation of the primitively eusocial ground-nesting bee Halictus farinosus were studied at Green Canyon, Utah from May to August, 2010. Nest architecture was typical of the genus. Nests were small with an average of 3.5 worker and 13.5 reproductive brood per colony. Most workers were mated (77.5%) and had ovarian development (73.4%). The queen-worker size differential was moderate (8.8% for head width and 6.2% for wing length), indicating that sociality in this species is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the bunchgrass prairie system, the two dominant late-season species were Lasioglossum incompletum and Halictus tripartitus, and in the riparian meadow system they were H. tripartitus and H. ligatus . All three species are primitively eusocial generalists (Packer et al 2007; Minckley 2008; Sheffield et al 2014; Kremen and M'Gonigle 2015; Ponisio et al 2019). The ubiquitous range of these particular species of sweat bees and their dominance in bee communities have been documented in several other studies in North America (Packer et al 2007; Richards et al 2011; Ponisio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bunchgrass prairie system, the two dominant late-season species were Lasioglossum incompletum and Halictus tripartitus, and in the riparian meadow system they were H. tripartitus and H. ligatus . All three species are primitively eusocial generalists (Packer et al 2007; Minckley 2008; Sheffield et al 2014; Kremen and M'Gonigle 2015; Ponisio et al 2019). The ubiquitous range of these particular species of sweat bees and their dominance in bee communities have been documented in several other studies in North America (Packer et al 2007; Richards et al 2011; Ponisio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All three species are primitively eusocial generalists (Packer et al 2007; Minckley 2008; Sheffield et al 2014; Kremen and M'Gonigle 2015; Ponisio et al 2019). The ubiquitous range of these particular species of sweat bees and their dominance in bee communities have been documented in several other studies in North America (Packer et al 2007; Richards et al 2011; Ponisio et al 2019). At least two of these species ( L. incompletum and H. tripartitus ) appear to be fairly robust in the face of disturbance, being found in high quality and highly disturbed habitat alike (Sardiñas et al 2016; Ponisio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There have been suggestions that such aggregations are formed, at least in some species, to increase defenses against natural enemies (Michener et al, 1958;Sakagami & Michener, 1962;Michener, 1974). Such aggregations also result from a tendency for young adults to return to the vicinity of their natal nests (Albert & Packer, 2013;Michener, 1966). Michener et al (1958) have confirmed that groups appear as a result of innate aggregative factors of the bees in response to preferences of habitat requirements.…”
Section: Nesting Sitementioning
confidence: 98%